Annual Report Year 6. - Feed the Future Innovation Lab for Nutrition. (Tufts University. Tisch Library., 2018)
The Annual Report submitted to USAID is a summary of the program's activities, research endeavors, capacity building projects, successes, challenges, solutions, and academic outputs. This report covers the Nutrition Innovation Lab's work in year 6.; Keywords: USAID, Nutrition, Annual Report, Uganda, Stunting, Aflatoxin, Agriculture.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy